Associations between obesity and physical activity in dogs: a preliminary investigation. (9th October 2013) - Morrison, R.; Penpraze, V.; Beber, A.; Reilly, J. J.; Yam, P. S.
Abstract : Objectives: To assess whether obesity has any association with objectively measured physical activity levels in dogs . Methods: Thirty‐nine dogs wore Actigraph GT3X accelerometers (Actigraph) for 7 consecutive days. Each dog was classified as ideal weight, overweight or obese using the 5‐point body condition scoring system. Total volume of physical activity and time spent in sedentary behaviour, light‐moderate intensity physical activity and vigorous intensity physical activity were compared between body condition categories . Results: Valid accelerometry data were returned for 35 of 39 dogs recruited. Eighteen dogs were classed as ideal weight, 9 as overweight and the remaining 8 as obese. All dogs spent a significant proportion of the day sedentary and obese dogs spent significantly less time in vigorous intensity physical activity than ideal weight dogs (7 ±3 minute/day versus 21 ±15 minute/day, P=0·01) . Clinical Significance: Obesity is associated with lower vigorous intensity physical activity in dogs, as is also thought to occur in humans. These preliminary findings will help inform a future, larger study and may also improve our understanding of the associations between obesity and physical activity in dogs .